OK ka ba TIYAN? (Oplan Kalusogan, KArunungan at BAyanihan Tungo sa Ikauunlad ni Yong mga Ati Naming kababayan) - Andan, Julie Jane F.; Ayongao, Jamela K.
World Health organization reports that diarrhea is the fourth leading cause of deaths among children less than five years old and the third leading cause of illness among the children. Philippine ranks second among thirteen countries included in the census in terms of the number of diarrhea cases causing 10,000 death every year. Main factors in the transmission of diarrheal diseases are: children not washing their hands due to lack of access to water and basic sanitation facilities, poor hygienic practices, and handed down practice from parents. Experts note that the incidence of diarrhea may easily be lowered by simply having kids wash their hands with water and soap. Therefore, the purpose of this project is to introduce to the community ways and means of preventing and managing diarrheal diseases by boosting the level of knowledge and introducing hygienic practices through the development of community-wide education programs that range from promoting healthy lifestyles in order to prevent disease, and providing the community with safe potable water supply in Purok V-Serum Bukid, Barangay San Nicolas, Buenavista, Guimaras. Efficient uses of health services, adopt self-care practices, and active participation in the design and implementation of health programs were also promoted.